Relation between Cancer and Germ Cells - Elizabeth Jeya Vardhini Samuel (Highlights on Medicine and Medical Research Vol. 2, 2021)
Background: Era of contraception, abortions, [20th, 21st centuries] implemented as family welfare schemes witnessed, increased global incidence of cancer, tumors, neoplasm and mortality. Objectives: Altruistic association of contraception [if any], with increasing cancer, tumor was sought after. Methods: In 2012, retrospective analysis of, prevalence of cancer, tumor in 350 patients of 20 - 35 years, 35 - 50 years, >50 years age groups, from data collected by convenient, stratified random sampling, from different geographical locations, between 2002-2012 and its association with presence, absence of contraception, abortion was undertaken; simultaneously, serum estrogen levels obtained from 105 patients, were also analyzed. From 1983-2012 clinical practice, 212 patients treated for different types of neoplasm namely breast cancer, prostate cancer, cancer cervix and benign prostatic hyperplasia were randomly allotted to the above 3 age groups and the data were analyzed for association with contraception status and possible significance. Results: 6 fold increase in cancer incidence was seen in contraceptive users among >50 years with a p value of <0.0005. Contraception was associated with 4 - 7 fold increase in tumor prevalence among >35 - >50 years with a p value of <0.0005. Endogenous estrogen had decreased to 5-8 pg in 61% of contraceptive users with a p value of <0.0005; after hysterectomy endogenous estrogen values up to 0.4 pg were seen. Cholesterol deprived diet, due to decreased synthesis of endogenous estrogen: androgen also was associated with 50% increase in tumor, cancer in youth without contraception. Estrogen receptors were positive in well differentiated cancers of breast, associated with reduced levels of endogenous estrogen among contraceptive users, suggesting estrogen receptor positivity could be a compensatory phenomenon; anaplastic tumors did not exhibit estrogen receptor positivity. 10 - 20 fold increase in breast cancer was seen among 20 - >50 years, in contra- ceptive users with a p value of <0.0005; 20 - 30 fold increase in prostate cancer was seen among 35 - >50 years, in contraceptive users with a p value of <0.0005; cancer of the cervix had increased 20 - 40 fold, among 20 - 70 years, in contraceptive users with a p value of <0.0005. Conclusion: Contraception of any form results in smashed fragmentation of germ cell to a centric fragments, ring chromosomes, chromatid breaks, generating auto immunity, significant reduction of endogenous, reproductive hormones, without which genomic repertoire: embryo like healing process defaults leading to 275% increased incidence of diseases, including cancers. Concept is acquired contraception preventing traversal of normal path by germ cells with resultant smashed destruction of germ cells, consequent reduced endogenous estrogen:androgen surveillance, leading to agonizing faults of cellular genomic repertoire, uncontrolled multiplication preceded by no differentiation of cell cycle, metabolism, resulting in soaringly high incidence of cancers including breast, prostate and uterine cervix in both life partners. Increased estrogen receptors:androgen receptors in breast, prostate well differentiated cancers respectively are, probably a compensatory rise, secondary to the sudden artificially acquired contraception resulting in significant reduction of endogenous germ cell hormones in contraceptive users. Contraception reversal with chemotherapy, radiation therapy, surgery achieves arrest of progression of cancer, reduces incidence, prevalence of neoplasm, as a cause-effect phenomenon and not castration or anti estrogen: antiandrogens which will perpetuate, promote neoplastic diseases by decreasing endogenous estrogen: androgen.